Acute Pneumothorax. Issue 2 (April 2016) - Arshad, Hammad; Young, Meilin; Adurty, Rajashekar; Singh, Anil C.
Abstract : Pneumothorax is defined as the abnormal presence of air within the pleural space (cavity) that results in the partial or complete collapse of a lung. It can occur spontaneously or due to a traumatic event. Symptoms can vary from a nondescriptive complaint of shortness of breath or chest pain to complete cardiopulmonary collapse. Diagnosis is based on a combination of clinical suspicion along with supporting imaging studies. Treatment often involves surgical or nonsurgical approaches with goal to alleviate symptoms and prevent recurrence.